Evaluasi Pembelajaran Mata Kuliah Audit Pada Mahasiswa Politeknik Negeri Bengkalis - Suharyono, Suharyono (Universitas Negeri Makassar, 2021)
This research was conducted to answer doubts over the competence of students in the field of auditing at D4 Public Financial Accounting Study Program, Bengkalis State Polytechnic. This study aims to compare learning outcomes and student competencies and learning business performance in the audit course for one semester. All students who have taken the audit course become the population as well as the sample in the study to ensure that the results obtained in the study will represent the whole student without exception. Based on the SPSS output on the Mann Whitney nonparametric statistical difference test, the sig result is 34.8%. The sig number of 34.8% is certainly greater than the alpha value of 5%. Thus, it is clear that based on the evaluation of the learning outcomes of the audit course between class A and class B students of the Bengkalis State Polytechnic Public Financial Accounting Study Program, there is no difference. This proves that the teaching methods that have been applied in the lecture process have improved students 'skills and knowledge in the field of audit, both in class A and in class B. A good lecture process or knowledge transfer even though it is in a different class will have an impact on increasing the knowledge and competence of students in auditing the financial statements of a company